Research of the Workspace Boundary Solving and Flexibility of 3-RRR Planar Parallel Robot - Cao Liya; Cui Jiankun; Song Yanan (Jixie chuandong)
A circular search algorithm for solving the spatial boundary of the planar parallel robot is proposed which is based on the iterative search method,and its flexibility index is analyzed. A series of boundary points for the workspace of the 3- RRR planar robot are determined by using the circular search algorithm depending on the existence of the inverse solution of the system. The results are consistent with the results by using geometric method. The restricted,dimension consistent Jacobian matrix can be obtained by using the speed of the end effector to represent the movement of the mechanism,which can measure the flexibility of the planar parallel robot,and with help of the Matlab graphics,the new Jacobi condition number distribution in the working space is intuitively reflected. According to the obtained Jacobian matrix,the more accurate flexibility indexes can be got.